2015
DOI: 10.1007/s11069-015-1875-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate adaptation at what scale? Multi-level governance, resilience, and coproduction in Saint Louis, Senegal

Abstract: This paper utilizes a multi-level governance framework to explain how and at what scale climate adaptation, exemplified by flood risk management, was governed in the medium-scale city of Saint Louis, Senegal. It explores how this policy sector worked toward a ''resilient city'' pointing to gaps between governance as prescribed and as practiced. The paper suggests that strong coordination of climate change adaptation and flood risk management should take place at city level, reflecting the ''place-based'' chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
(54 reference statements)
2
36
0
2
Order By: Relevance
“…In brief, discussions with Tuong Van residents and governmental staff revealed weak collaboration among actors across multiple levels, which in turn limited efforts to reduce climate risks at the community level over the last three decades. These findings not only add to the knowledge about shortcomings of weak collaboration on climate risk management, but also support a growing body of research that highlights the importance of strong collaboration in producing mutual and collective supports to address complex issues stemming from a changing climate (Djalante et al 2013, Vedeld et al 2015.…”
Section: Collaborationsupporting
confidence: 69%
See 2 more Smart Citations
“…In brief, discussions with Tuong Van residents and governmental staff revealed weak collaboration among actors across multiple levels, which in turn limited efforts to reduce climate risks at the community level over the last three decades. These findings not only add to the knowledge about shortcomings of weak collaboration on climate risk management, but also support a growing body of research that highlights the importance of strong collaboration in producing mutual and collective supports to address complex issues stemming from a changing climate (Djalante et al 2013, Vedeld et al 2015.…”
Section: Collaborationsupporting
confidence: 69%
“…Research elsewhere concluded weak coordination as a critical barrier to climate risk management (Vedeld et al 2015). For example, devastating losses from the 2005 Hurricane Katrina resulted from the disarray in emergency management systems (Waugh Jr and Straib 2006).…”
Section: Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact in other sub-Saharan countries, our results suggest the project-based interventions such as the LWW programme tend to put more emphasis on short-term impacts on absorptive capacity aspects, while adaptive and anticipatory capacity components require longerterm approaches to be consolidated [11,22,43]. This explains why their effects are difficult to appreciate in the longer term, especially because monitoring of impacts usually end with the interventions themselves in such international programmes.…”
Section: Discussionmentioning
confidence: 88%
“…required at regional to local levels to tackle 'vulnerability hotspots' where climate change impacts are particularly significant (Rannow et al, 2010). The capacity of, and interplay between, regional and local level institutions often plays a role in the functioning of multilevel governance and actions to promote such targeted policy (Hanssen et al, 2013;Vedeld et al, 2016). These considerations have resulted in a rapidly growing number of initiatives to develop lower level climate change responses, e.g., the 'Mayors Adapt' (http://mayors-adapt.eu/) and the '100 Resilient Cities initiative' (http://www.100resilientcities.org/).…”
mentioning
confidence: 99%